Development information system of HIV/AIDS for drug users, 2010-2011 - ภาวนาภรณ์ วิภา (Disease Control Journal, 2014)
This Study aims to develop information system on HIV/AIDS among drug users in public and private drug treatment unit/network. The information system was developed during the year 2010 - 2011. It comprised of two phases; the first phase is the development of the written form type of data collection on prevention and care services for drug users at 15 drug treatment units; the second phase is the development of the computer based type of data collection with instruction manual and training for service providers to collect data on prevention and care services for drug users at 10 drug treatment units. Computer-based data analysis showed that 879 drug users came for services, 93.3% were males and 6.7°/o were females, 40% were aged between 16-25 years. For route of drugs administration; 19.6% reported using intravenous drugs and 12.9% did not use new injection equipment on their last usage. It is shown that 53.3% of the drug users correctly answered every question on basic HIV prevention knowledge test. Up to 74.7 % reported not using condoms on their last sexual intercourse with their partners. For HIV prevention and care services; 27.5% of the drug users were screened for HIV infection and 5.5% were infected. It is reported that 61.5% of the drug users were aware of Drug Treatment Units that provide free condoms and 59.8% were aware of Drug Treatment Units that provide new injection equipment. However, only 13.6% were aware of the places that they can have blood test for HIV infection. Computer based data collection was found favorable by service providers, 60% reported very high satisfaction and 40% reported high satisfaction. It covered all information required for HIV surveillance among drug users and enabled immediate information transfer directly to the Bureau of AIDS TB and STIs for national data analysis. Integration of HIV/AIDS prevention /control program into Drug User Treatment Program provides sustainable solution in talking HIV/AIDS among drug users. Adequate information with effective information system is crucial in providing direction for developing work plan to combat the problem